Development of Enterprise Architecture Model for Smart City - Saluky Saluky (ITEJ (Information Technology Engineering Journals), 2017)
Population development is so fast and half within the city that it creates social problems. In addition, the city also has future challenges such as population growth, poverty, health, safety, energy needs, and pollution levels. The problems and challenges of the city must get the solution through the use of the smart city concept in managing the city. Smart City is a city with a development concept using existing resources effectively and efficiently and can be used to maximize the benefits of citizens through the use of information and communication technology. To build a smart city It takes enterprise architecture as a medium of communication by all the intelligent city stakeholders that can be achieved in accordance with predetermined goals. This research aims to develop the enterprise architecture model by using TOGAF to be used and provide solutions to the problems and challenges of the city through the development of enterprise smart city architecture. The results show that Smart City Enterprise Architecture developed using TOGAF can be used as a reference for smart city development.